Anatomic relationship of the sural nerve when performing Achilles tendon repair using the percutaneous Achilles repair system, a cadaveric study. Issue 4 (June 2021) - McGee, Roddy; Watson, Troy; Eudy, Adam; Brady, Candice; Vanier, Cheryl; LeCavalier, Daniel; Hoang, Victor
Highlights: Minimally invasive techniques for Achilles tendon repair are increasing due to less complications compared to open repair. The anatomy of the sural nerve maintains a variable course in its distribution. There is potential risk for sural nerve injury when using percutaneous techniques for Achilles tendon repair. Limited incision surgery can be a safe and effective technique with few complications when the technique is used correctly. Abstract: Background: Minimally invasive techniques for Achilles tendon repair are increasing due to reports of similar rerupture rates using open and percutaneous techniques with fewer wound complications and quicker recovery with percutaneous methods. The goal of this study was to investigate quantitatively the relationship and risk of injury to the sural nerve during Achilles tendon repair when using the Percutaneous Achilles Repair System (PARS) (Arthrex®, Naples, FL), by recording the distance between the passed needles and the sural nerve as well identifying any direct violation of the nerve with needle passage or nerve entrapment within the suture after the jig was removed. The hypothesis of the study is that the PARS technique can be performed safely and without significant risk of injury to the sural nerve. Methods: A total of five needles were placed through the PARS jig in each of 10 lower extremity cadaveric specimens using the proximal portion after simulation of a midsubstance Achilles tendon rupture. Careful dissection was performed to measure the distance of the sural nerve in relation to the passed needles. The sutures were then pulled out through the incision as the jig was removed from the proximal portion of the tendon and observation of the suture in relation to the tendon was documented. Results: Of the 10 cadaveric specimens, none had violation of the sural nerve. Zero of the 50 (0%) needles directly punctured the sural nerve. In addition, upon retraction of the jig, all sutures were noted to reside within the tendon sheath with no entrapment of the sural nerve noted. Conclusion: This study demonstrated the variable course of the sural nerve and identifies the potential risk for sural nerve injury when using the PARS for Achilles tendon repair. However, this study provides additional evidence of safety from an anatomic standpoint that explains the outcomes demonstrated in the clinical trials. With this information the authors believe surgeons should feel comfortable they can replicate those outcomes while minimizing risk of sural nerve injury when the technique is used correctly.